Entomopathogenic fungi as the microbial frontline against the alien Eucalyptus pest Gonipterus platensis in Brazil - Jordan, Carolina [UNESP]; dos Santos, Paula Leite [UNESP]; Oliveira, Leiliane Rodrigues dos Santos [UNESP]; Domingues, Mauricio Magalhães [UNESP]; Gêa, Bianca Cristina Costa [UNESP]; Ribeiro, Murilo Fonseca [UNESP]; Mascarin, Gabriel Moura; Wilcken, Carlos Frederico [UNESP] (Springer Nature, 2021)
The eucalyptus snout beetle (ESB), Gonipterus platensis, is endemic to Australia but has become a major invasive, destructive pest of Brazilian eucalyptus plantations. Efforts to develop insecticides based on entomopathogenic fungi against ESB are limited by the lack of known virulent strains. We therefore explored the virulence of indigenous Brazilian strains of major entomopathogenic fungi—Beauveria spp. and Metarhizium anisopliae—against ESB adults. We found widely varying virulence and later capacities for conidial production on infected adult cadavers. Two strains stood out, B. bassiana IBCB-240 and M. anisopliae IBCB-364, as especially lethal for ESB adults under laboratory conditions, sporulated abundantly on infected insects, and also outperformed comparable strains used in commercial mycoinsecticides. Notably, B. bassiana IBCB-240 exhibited lower LT50 values at low inoculum levels (≤ 107 conidia mL−1) and smaller LC50 values than M. anisopliae IBCB-364. Taken together, this study emphasizes natural variation in virulence among indigenous Beauveria and Metarhizium strains against ESB adults and identifies fungal strains with superior lethality to existing commercialized strains for managing this eucalyptus pest in Brazil.